Water As a Medium to Reduce the Room Temperature on the Roster - Matthew, Nicholas Joe; Santosa, Hosea Alessandro; Putra, Heristama (Jurnal Riset Arsitektur, 2025)
Climate change and rising air temperatures in Surabaya require the implementation of building design strategies to maintain thermal comfort passively and sustainably. This study aims to assess the effectiveness of water as a cooling medium in a passive ventilation system based on clay rosters, with the theory of evaporative cooling and the thermal behavior of porous materials. The research method uses a quantitative experimental approach that refers to the concept of natural heat and moisture exchange in tropical building ventilation systems. Two conditions were tested, namely dry rosters and rosters flowed with water, to compare their thermal response to environmental temperature. The rosters were made of porous clay that functions as a natural evaporative medium, with a bottom-to-top water flow system circulated using a small pump. Temperature measurements were taken at certain time intervals using a digital thermometer. The test results show the roster system with water elements significantly reduce room temperature through the mechanism of water evaporation that absorbs heat from the surrounding air. The integration of the concepts of natural ventilation, evaporation, and porous materials such as rosters shows great potential as an effective, energy-efficient, and applicable architectural solution to improve the thermal comfort of tropical buildings.